2003
DOI: 10.1210/jc.2002-021190
|View full text |Cite
|
Sign up to set email alerts
|

α2B-Adrenergic Receptor Deletion Polymorphism Associates with Autonomic Nervous System Activity in Young Healthy Japanese

Abstract: Several polymorphisms of genes involved in autonomic nervous system (ANS) function have been reported to affect metabolic regulation. We have investigated the association of an alpha(2B)-adrenergic receptor (alpha(2B)AR) three-amino acid deletion polymorphism with ANS activity in young healthy subjects by means of electrocardiogram R-R interval power spectral analysis. Three hundred eighty-one young healthy Japanese males (mean +/- SE, 20.6 +/- 0.1 yr) were studied. One hundred sixty-eight (44.1%) were homozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 22 publications
1
47
0
3
Order By: Relevance
“…Sivenius et al (2001) investigated the short form of the Glu variant on changes in body weight in nondiabetic and type 2 diabetic subjects and found that the short allele was associated with an increase in body weight among nondiabetic subjects. More recently, in young, healthy Japanese individuals, no association among the deletion variant and body mass index, plasma glucose, or insulin concentrations, or family history of diabetes or obesity was found; however, the short allele was associated with low-and very low-frequency R-R spectral analysis of heart rate variability, as well as a significantly higher index of sympathetic nervous system activity and a lower index of parasympathetic nervous system activity (Suzuki et al, 2003). This alteration in ANS function may contribute to metabolic disorders.…”
mentioning
confidence: 99%
“…Sivenius et al (2001) investigated the short form of the Glu variant on changes in body weight in nondiabetic and type 2 diabetic subjects and found that the short allele was associated with an increase in body weight among nondiabetic subjects. More recently, in young, healthy Japanese individuals, no association among the deletion variant and body mass index, plasma glucose, or insulin concentrations, or family history of diabetes or obesity was found; however, the short allele was associated with low-and very low-frequency R-R spectral analysis of heart rate variability, as well as a significantly higher index of sympathetic nervous system activity and a lower index of parasympathetic nervous system activity (Suzuki et al, 2003). This alteration in ANS function may contribute to metabolic disorders.…”
mentioning
confidence: 99%
“…Todd et al, 2015). The reason may be differences in participant recruitment or differences in Higher incidences have been reported in East Asians: 68% of Chinese (Zhang et al, 2005); 56% of one group of Japanese (Suzuki et al, 2003) and 71% of another (Ishii et al, 2015). Among the Shors, a Turkic people of Siberia, the incidence was 73%.…”
Section: Affective Empathymentioning
confidence: 98%
“…Of these, 93 were subjects in our previous report (Suzuki et al 2003), and 56 subjects were newly recruited in the present study. The ages of subjects ranged from 18-31 years (21.3±0.2, mean± SEM).…”
Section: Study Populationmentioning
confidence: 99%
“…The R-R interval power spectral analysis procedures have been described previously (Matsunaga et al 2005;Nishikino et al 2006;Suzuki et al 2003;Yasuda et al 2006). Briefly, the ECG R-R interval data obtained from the CM5 lead were digitized at 1,000 Hz, and the derived R-R interval time series were then aligned in a 2-Hz sequence for power spectral analysis.…”
Section: Ecg R-r Interval Power Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation